The Effect of Art Therapy by Painting Technique on Social Function Level in Schizophrenia Patients at Menur Mental Hospital, Surabaya City, East Java, Indonesia - Adiba, Dimmi Maula Fara; Paramita, Hilma (International Medical Journal Corp. Ltd, 2024)
Background : Social disfunction is one of the main characteristic of schizophrenia. People with schizophrenia manifest disability in social skill and other aspects of social function. Art therapy by painting technique are able to decrease levels of anxiety, depression and stress in schizophrenia patients because patients can express their negative feelings through arts, therefore, it will improve their social function. Aim : The aim of this study was to know the effect of art therapy by painting technique on social function in schizophrenia patients at Menur Mental Hospital, Surabaya City, East Java, Indonesia. Method : This research was quasi experimental one group pretest-posttest design. Result : Research subject were 7 people. Social function was measured by GAF scale. Two sessions of therapy were given to the patients. Wilcoxon test showed p = 0,024 (p<0,05). Conclusion : This research showed that there were significant effect of art therapy by painting technique on social function of schizophrenia patients at Menur Mental Hospital, Surabaya City, East Java, Indonesia.